Review on the beneficial effects of omega-3 enriched eggs by dietary flaxseed oil supplementation - Keten, Mehmet (İstanbul Veteriner Hekimler Odası, 2019)
The aim of this review is to convey updated knowledge, for better decision making in preventive and therapeutic health care, as well as in agriculture and food industries. The association of omega-3 polyunsaturated fatty acids (PUFA) with cardiovascular risk was suspected early in Eskimo populations that are known to have a high consumption of fish and fish oil. However, their diet contained almost no vegetable foods. Omega-3 polyunsaturated fatty acids have been studied intensively as nutrients that protect against cardiovascular disease. Awareness of fatty acids beneficial effects seems to have played a role in creating new products labeled high in omega-3. Most of them use ALA (α-linolenic acid), derived from plants. Health effects of omega-3 fatty acids come mostly from EPA (eicosapentaenoic acid) and DHA (docosa-hexaenoic acid). It is not an efficient process for humans to synthesize EPA and DHA from ALA in contrast to laying hens. EPA and DHA Omega-3 enrichment of eggs with ALA rich flaxseed oil is an effective way.